2016
DOI: 10.1017/jfm.2016.102
|View full text |Cite
|
Sign up to set email alerts
|

Settling of heated particles in homogeneous turbulence

Abstract: We study the case of inertial particles heated by thermal radiation while settling by gravity through a turbulent transparent gas. We consider dilute and optically thin regimes in which each particle receives the same heat flux. Numerical simulations of forced homogeneous turbulence are performed taking into account the two-way coupling of both momentum and temperature between the dispersed and continuous phases. Particles much smaller than the smallest flow scales are considered and the point-particle approxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 54 publications
5
31
0
Order By: Relevance
“…cluster and create hot plumes of upward moving fluid, a phenomenon also observed in settling of hot particles through forced turbulence (Frankel et al 2016). In figure 23 the particle temperature versus the Froude number is also plotted.…”
Section: Effect Of the Finite Particle Froude Numbermentioning
confidence: 89%
See 2 more Smart Citations
“…cluster and create hot plumes of upward moving fluid, a phenomenon also observed in settling of hot particles through forced turbulence (Frankel et al 2016). In figure 23 the particle temperature versus the Froude number is also plotted.…”
Section: Effect Of the Finite Particle Froude Numbermentioning
confidence: 89%
“…The small peak observed in the particle temperature around Fr ≈ 1 can be attributed to the fact that at this regime the mean vertical velocity of the particles is almost zero, leading to higher residence time of the particles in the plumes. In a recent study of DNS of hydrodynamically forced turbulence laden with heated inertial particles (Frankel et al 2016), it was shown that the buoyant plume shed by the clusters breaks down the preferential sweeping mechanism by which particle settle faster as they favour the downward side of turbulent eddies (Wang & Maxey 1993).…”
Section: Effect Of the Finite Particle Froude Numbermentioning
confidence: 99%
See 1 more Smart Citation
“…In a turbulent flow, the sedimentation phenomenon does not depend only on characteristics of particles and fluid, but also on the Kolmogorov length and time scales which are related to the eddies (Fung ; Dejoan ; Frankel et al . ; Fornari et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…The real situation for industrial thickeners and settling tanks involves complex interactions between particles, flocculation and turbulence that substantially alter from one case to another. In a turbulent flow, the sedimentation phenomenon does not depend only on characteristics of particles and fluid, but also on the Kolmogorov length and time scales which are related to the eddies (Fung 1998;Dejoan 2011;Frankel et al 2014;Fornari et al 2015a,b). Basically, particles smaller than the Kolmogorov length behave differently than those larger than this scale.…”
Section: Introductionmentioning
confidence: 99%